Ergonomic assessment on work-related musculoskeletal disorders to improve quality and productivity of workers in woodworking industry in Malaysia - Mohd Hawari, Nurhanisah (2023)
Over the course of the twenty-first century, work-related musculoskeletal disorders (WMSDs) have persisted among blue collar workers. The primary aim of this study was to develop an anthropometric workstation design model that could reduce WMSDs and enhance comfort perception among industrial workers while performing their tasks. This study was conducted to investigate the needs and then design, develop, fabricate, and test a prototype of an industrial ergonomic trolley for industrial male workers. In the first phase, a self-administrated questionnaire was distributed to 232 industrial workers from Peninsular Malaysia. This was to determine the prevalence of WMSDs among industrial workers in Malaysia. The result showed that the prevalence of WMSDs among industrial workers was 93.1%. Furthermore, it showed that the most affected part of the body was the lower back, with 62.1%, caused by industrial workers’ job tasks. The most significant risk factors associated with body parts were gender, age, working hours, and most difficult tasks with MSDs, especially in the lower back. A survey on musculoskeletal pain and discomfort associated with work condition, sleep health, and social life in the second sequence was carried out via a selfadministrated questionnaire. 54 industrial workers were chosen randomly from factories and rehabilitation centers to describe the MSDs pain and discomfort related to the work, life and sleep of industrial workers. The obtained results indicated that the lower back experienced the most prevalent pain caused by work conditions, sleep health, and lifestyle. Musculoskeletal discomfort of woodworkers was evaluated using Rapid Entire Body Assessment (REBA) and Quick Exposure Check (QEC) in the third phase. This was to investigate the exposure of risk factors for WMSDs in woodworkers across four main tasks of cutting, lifting, assembling, and finishing products. The study was conducted among 30 workers in three woodworking workshops in Selangor, Malaysia. Throughout this phase, the demographic surveys, QEC, and REBA were examined. The results indicated that the most critical tasks were lifting and assembling. Hence, the recommendation for this study was to design a product to control the hazards. The design and development of the anthropometric workstation in the third phase and fourth sequence was carried out using anthropometric data obtained from woodworkers performing the lifting task. This study measured anthropometric dimensions of six industrial male workers. Four anthropometrics measurements including stature height, arm span, arm reach forward, and waist height were taken. The average height at 50th percentile was chosen to design the industrial ergonomic trolley for the wood furniture industry. Lastly, the validation of the design of the industrial ergonomic trolley was evaluated by REBA, QEC and interview session involved with ten male workers. The results showed that the industrial ergonomic trolley appeared to be a good design for industrial workers to reduce movement of the body posture in their daily lifting activity. In a nutshell, this study achieved the goal to design and develop an anthropometric workstation model that enhances the comfort perception and improves the quality and productivity of industrial workers.